Oracle HTML DB handbook - Linnemeyer, Lawrence (McGraw-Hill, 2006)
Develop and deploy fast, secure web applications. Even if you have limited programming experience, you can develop and deploy professional-quality applications using Oracle's new rapid web application development tool. "Oracle HTML DB Handbook" shows you how to quickly create secure and scalable web applications that can be instantly deployed. Learn how you can consolidate spreadsheets and desktop databases into an Oracle Database and share your applications over the web. You'll also get details on administration and security. Real-world sample projects get you started using Oracle HTML DB right away.Install and configure Oracle HTML DB. Work with Oracle database objects using SQL Workshop. Create, review, edit, run and delete application elements with the HTML DB Application Builder. Work with themes and templates. Create, edit, and delete HTML DB pages. Work with reports and process forms. Implement navigational elements in applications. Administer and manage applications and users. Add computations, processes, and validations to applications. Implement HTML DB security measures